Model Blended Learning Pendekatan Contextual Teaching Learning (BLCTL) Pada Mata Kuliah Keperawatan Dasar Bagi Mahasiswa Keperawatan - Musrifatul Uliyah; Abdul Aziz Alimul Hidayat (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The competencies of nursing education graduates that are of concern are basic nursing knowledge, collaboration skills, and adaptive thinking. The efforts to overcome these competencies are through learning that can construct knowledge, encouraging collaboration and adaptive abilities. The process of constructing knowledge, collaboration and adaptive skills can be got from two learning models, namely face-to-face and e-leaning, with emphasis on contextual aspects, collaborative and adaptive elements. This research aims to analyze the feasibility of a blended learning model with a contextual teaching learning (BLCTL) approach in learning basic nursing courses for nursing students. Methods: research and development was used in this study, using the Dick and Carey Model, with a sample size of 104 selected using simple random sampling from students in the Nursing Program at Muhammadiyah University, Surabaya. Data was collected at the model needs analysis stage using for and observations, the development stage using questionnaires, the implementation stage using tests and observations. Results: The research results show that the BLCTL model is a learning model that is suitable for the learning process with a learning syntax comprising 5 phases, namely constructivism, questioning and inquiry, learning community, modeling, and authentic assessment and reflection. With the results of the model feasibility test on the learning model aspect 97.1%, RPS learning device aspect 97.9%, media device (e-learning) 96.6%, textbook device 95.8%, knowledge assessment and collaboration device 100%. Conclusion: The BLCTL model involves students in the learning process, which identifies previous knowledge and learning experiences for the learning activity process. By emphasizing actual conditions and existing characteristics, this model is very relevant to learning in nursing education and the development of information technology to create an adaptive learning system.